Stranglehold - Johnstone, William W; Johnstone, J. A (Pinnacle western., 2019)
Here in America, life is full of surprises. Duff never expected to hear from his old friend Charles McGregor, his batallion commander from the Black Watch Regiment of Her Majesty<U+2019>s army. Turns out McGregor lives in New Mexico now. And he needs Duff<U+2019>s help. He<U+2019>s started a new life as the mayor of Antelope Wells<U+2014>a mining town that<U+2019>s being targeted by a power-hungry madman Ebenezer Schofield, who wants to declare the whole area an independent principality<U+2014>and himself as king. He<U+2019>s already squeezing taxes out of the local businesses and citizens. But no one has the guts to stop him. Because Parker<U+2019>s got his own private army of fifty uniformed men, six Mexican revolution cannons<U+2014>and a traitor working on his side in the heart of Antelope Wells . . . This is more than just a favor for a friend. This is justice. This is payback. This is war. And this is Duff MacCallister.